Influence of psoriasis lesions' location and severity on psychosocial disability and psychopathology. Observational study and psychometric validation of the SAPASI Portuguese version - Teixeira, Ana (2022)
Objectives: The psychosocial impact of psoriasis is well documented. However, the contributing role of clinical disease characteristics is not satisfactorily explored. This study aimed to validate the Self-administered Psoriasis Area and Severity Index (SAPASI) to a Portuguese population (SAPASI-PT) and to perform its cross-validation, assessing how the results will generalize to an independent data set, with the Psoriasis Area and Severity Index (PASI), in order to assess the influence of psoriasis’ severity on psychosocial disability and psychopathology. Methods: A cross-sectional study with 228 patients with psoriasis was carried out. Data was collected through a sociodemographic and clinical questionnaire, SAPASI-PT, the Psoriasis Disability Index (PDI) and the Brief Symptoms Inventory (BSI). The cultural and linguistic adaptation of SAPASI to a Portuguese version and the cross validation with PASI was carried out. Multiple associations between psychosocial disability, psychopathology and severity, discomfort and location of lesions were investigated through logistic regression models. Results: A good adjustment model for SAPASI-PT is found. Also, associations between psychosocial disability, psychopathology and the psoriasis severity and discomfort are found. The existence of lesions is positively associated with the severity of the disease. Patients with lesions in hands or genitals are those reporting a greater discomfort. The presence of lesions in hands is positively associated with PDI, i.e., with leisure and with treat ment, marginally. Additionally, patients scoring higher in the personal dimension are found to have a signifi cantly greater percentage of lesions in the genitals. Conclusions: The psoriasis severity and location of lesions are important determinants of patients´quality of life. Lesions on face, hands and genitals are associated with a higher impact on psychosocial wellbeing of patients. Psychological counselling should be considered within psoriasis treatment context in patients with the described disease manifestations.